Growth-Pattern of School Children in the Best Circumstanced Schools in Bandung - A.H. Pallencaoe; H. Permadhi; D. Danoemoelia; S. Wiradisuria (Paediatrica Indonesiana, 1979)
Recently a team approach is suggested in health care delivery to the community. Simple methods in evaluating health by professions other than the medical profession have to be designed. The teacher is the best person besides the medical personnels to be also involved in promoting the physical health of the school children. In order to assess this, a standard percentile distant curve growth chart drawn relevant to the local socio-economic condition is required. In developing countries a growth chart of the best nourished and circumstanced local group is suggested to be used as a standard (Tanner, 1973). The aim of this study is to provide the teacher such a growth chart. The subjects consisted of 10.342 pupils from 32 selected schools, from which centiles curves were drawn. The percentile curves showed that the 90 centile is below the 50 centile and the 50 centile below the 10 centile of the Harvard Standard.